A nomogram incorporating six easily obtained parameters to discriminate intrahepatic cholangiocarcinoma and hepatocellular carcinoma. (23rd February 2018) - Wang, Mengmeng; Gao, Yuzhen; Feng, Huijuan; Warner, Elisa; An, Mingrui; Jia, Jian'an; Chen, Shipeng; Fang, Meng; Ji, Jun; Gu, Xing; Gao, Chunfang
Abstract: Intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC) are the most prevalent histologic types of primary liver cancer (PLC). Although ICC and HCC share similar risk factors and clinical manifestations, ICC usually bears poorer prognosis than HCC. Confidently discriminating ICC and HCC before surgery is beneficial to both treatment and prognosis. Given the lack of effective differential diagnosis biomarkers and methods, construction of models based on available clinicopathological characteristics is in need. Nomograms present a simple and efficient way to make a discrimination. A total of 2894 patients who underwent surgery for PLC were collected. Of these, 1614 patients formed the training cohort for nomogram construction, and thereafter, 1280 patients formed the validation cohort to confirm the model's performance. Histopathologically confirmed ICC was diagnosed in 401 (24.8%) and 296 (23.1%) patients in these two cohorts, respectively. A nomogram integrating six easily obtained variables (Gender, Hepatitis B surface antigen, Aspartate aminotransferase, Alpha‐fetoprotein, Carcinoembryonic antigen, Carbohydrate antigen 19‐9) is proposed in accordance with Akaike's Information Criterion (AIC). A score of 15 was determined as the cut‐off value, and the corresponding discrimination efficacy was sufficient. Additionally, patients who scored higher than 15 suffered poorer prognosis than those with lower scores, regardless of the subtype of PLC. A nomogram for clinical discrimination of ICC and HCC has been established, where a higher score indicates ICC and poor prognosis. Further application of this nomogram in multicenter investigations may confirm the practicality of this tool for future clinical use. Abstract : Confidently discriminating ICC and HCC before surgery can improve both treatment and prognosis. The authors have used a large‐scale study to construct a simple nomogram model incorporating six easily obtained parameters, which demonstrates high accuracy (AUC >0.85) when compared with clinical histologic examination.